A size-shrinkable nanoparticle-based combined anti-tumor and anti-inflammatory strategy for enhanced cancer therapy. Issue 21 (17th May 2018) - Lu, Zhengze; Long, Yang; Cun, Xingli; Wang, Xuhui; Li, Jianping; Mei, Ling; Yang, Yiliang; Li, Man; Zhang, Zhirong; He, Qin
Abstract : The co-administration of RDDG and RMDG NPs simultaneously inhibits the tumor growth and the cancer-related inflammation. Abstract : Cancer-related inflammation can promote tumorigenesis, tumor growth and tumor metastasis in many types of cancers. Therefore, inhibiting cancer-related inflammation significantly improves cancer therapy. It has been reported that metformin (MET) inhibits the nuclear translocation of nuclear factor-κB (NF-κB), a key factor in cancer-related inflammation. However, the short half-life and the lack of tumor targeting limit the anti-inflammatory efficacy of MET in vivo . Herein, using pH-sensitive imine bonds, MET and the chemotherapy drug doxorubicin (DOX) were loaded onto size-shrinkable RGD-DGL-GNP nanoparticles (RDG NPs) for combination therapy. The RGD-MET-DGL-GNP nanoparticles (RMDG NPs) penetrated deep into the tumor to deliver MET and inhibit the NF-κB activity in tumor cells, which further decreased tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) expressions in tumor tissues and suppressed tumor cell proliferation. As a result, the co-administration of RGD-DOX-DGL-GNP (RDDG NPs) and RMDG NPs induced an improved therapeutic effect in a xenograft tumor model and a lipopolysaccharide (LPS)-induced pulmonary metastasis model with murine 4T1 breast cancer and CT26 colon cancer cells. Combining RDDG and RMDG NPs to simultaneously target tumors and cancer-related inflammation is a very effective anti-cancer strategy.